2015
DOI: 10.1016/j.technovation.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Distant recombination and the creation of basic inventions: An analysis of the diffusion of public and private sector nanotechnology patents in Canada

Abstract: Document publié chez l'éditeur commercialDocument issued by the commercial publisher Mention légale:Legal notice:In all cases accepted manuscripts should link to the formal publication via its DOI AbstractThis article explores whether the relationship between the breath of technological integration (recombination distance) and the breath of an invention's subsequent application (basicness) is moderated by the sector of activity (private or public), sciencelinkage strength and industry characteristics. Our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 149 publications
(171 reference statements)
0
10
0
Order By: Relevance
“…For reasons we explain in the next section, we do not attempt to empirically examine long search paths with patent data and instead rely on theory and the qualitative statements that arose from the inventor interviews. There have been previous studies that have considered the role of scientific reasoning in unusual discoveries (e.g., Fleming and Sorenson 2004) and distant recombination (e.g., Barirani et al 2015, Keijl et al 2016. Our paper, however, is the first we know of to articulate and explore the role of long search paths in outlier patents, to compare multiple search processes that may result in outlier discoveries, and to disentangle the roles of individual breadth of experience and team breadth of experience in distant recombination.…”
Section: Knowledge Creation and Technological Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…For reasons we explain in the next section, we do not attempt to empirically examine long search paths with patent data and instead rely on theory and the qualitative statements that arose from the inventor interviews. There have been previous studies that have considered the role of scientific reasoning in unusual discoveries (e.g., Fleming and Sorenson 2004) and distant recombination (e.g., Barirani et al 2015, Keijl et al 2016. Our paper, however, is the first we know of to articulate and explore the role of long search paths in outlier patents, to compare multiple search processes that may result in outlier discoveries, and to disentangle the roles of individual breadth of experience and team breadth of experience in distant recombination.…”
Section: Knowledge Creation and Technological Searchmentioning
confidence: 99%
“…One of the ways that inventors might create inventions that appear distant from known inventions is through distant recombination-that is, a combination that fuses two or more disparate knowledge domains (see Figure 1, panel (d) and Table 3). Other studies have similarly posited that distant recombination might lead to inventions that are more basic or fundamental in their nature, or that have greater impact (e.g., Barirani et al 2015, Keijl et al 2016). An excellent example is the development of the camera pill.…”
Section: Distant Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in the fields of information science and business management have designed multidimensional evaluation systems for analyzing competitive relations based on patent data. Common indicators include: the number of patents (used for measuring the scale of technological innovation), the patent application area (used for identifying the target market of enterprises), the International Patent Classification (IPC) or U.S. Patent Classification (UPC) (used for discovering the focus of technology R&D of enterprises), the number of invention patents or tripartite patents (used for evaluating enterprise's technical quality), the forward reference of the patent (used for evaluating the technical influence of enterprises), the back reference of the patent (used for determining technical originality), and so on [23][24][25]. Jaffeused the sales revenue of each product category to measure the proximity of technology positioning among enterprises [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patents are an important indication of the originality and creativity of knowledge (Schoenmakers and Duysters, 2010). Barirani et al (2015, p. 40) suggested that “since patents are granted to inventions that are novel, non-obvious and useful, they can generally be viewed as indicators of technological change and innovative activity.”…”
Section: Literature Reviewmentioning
confidence: 99%